IMPLEMENTASI KEBIJAKAN PUSAT KONSELING ANAK DAN REMAJA DI SURABAYA - RIO FEBRIANNUR RACHMAN (Universitas Islam Negeri Mataram, 2019)
There are many steps taken by the City Government of Surabaya to solve the problems of children and adolescents. This article focuses on discussing how the counseling center, which aims to address these problems, provides concrete services in the community. This discussion uses public policy theory and the principle of sustainable social development that is agreed internationally by countries in the world. The method used is qualitative, with a literature review approach. The results of the study indicate that the policies of the counseling center for children and adolescents, in line with universal Islamic and humanist values. However, there must be improvements to the program mechanism as the demands of the situation nowadays.